Penguasaan Bentuk Kalimat Perfekt - Muh. Satria; Hasmawati Hasmawati; Syukur Saud (Phonologie : Journal of Language and Literature, 2021)
Abstract. The purpose of this study was to obtain data on mastery in making perfect sentences for class XII IIS students of SMA Negeri 11 Makassar. This research is quantitative descriptive. The population of this study was the 106 students of class XII IIS SMA Negeri 11 Makassar. The sample of this study used a random sampling technique, namely the 36 students of class XII IIS 1 SMA Negeri 11 Makassar. The results of data analysis using the percentage technique. The results of this study indicate that the level of mastery of the perfect sentence form of class XII IIS SMA Negeri 11 Makassar is 67% enough.